A representação social do saber de trabalhadores rurais sobre o controle de parasitos em propriedades produtoras de leite - Ana Cristina Passos de Paiva Bello (2010)
Within milk producing economic losses stem mainly from endo and ectoparasites frames in herds, and also the high cost for the misuse of pesticides. This investigation aimed to evaluate the new technologies for strategic control of integrated endo and ectoparasites of cattle and horses implementation during milk-producing farms routine. Through this work we concluded that the successful strategic control implementation in commercial property is directly related to the human dynamics relationships, which create bottlenecks in this process in the field, which are only detected when one understands the socio- intertwined in the economic and cultural production system, which need further investigation to identify them. Parasites, worms and ticks in dairy cattle, were regarded by respondents as the major problems of health of their production systems. The transferring the integrated strategic process was partially assimilated by the actors involved in the project. Access to information, technical administrative management, the operation, the skilled manpower supply, level of education and economic, cultural and psycho-social characteristics, interfere in the transfer process and implementation of new technologies on farms.